POLA KERJASAMA KELOMPOK USAHA BUDIDAYA JAMUR MERANG DI KELURAHAN POHJENTREK, KECAMATAN PURWOREJO KOTA PASURUAN - F. Kasijadi; Rikawanto Eko Mulyawan; Ery Yusnita Arvianti (Universitas Tribhuwana Tunggadewi, 2007)
A study aimed to judge earnings and efficiency of mushroom cooperative farming was conducted at Puworejo District of Parusuan Regency. Primary data was collected from all 20 farmers involved in the farming. All data related to mushroom farming was collected using questionnaires combine with field visits. Results of this study revealed that based on production, revenue, earnings and costs, the cooperative mushroom farming was efficient to carry on. This was indicated by revenue: cost ratio of 1.59 at nucleus and 1,74 for plasma for one production cycle in the cooperative system